Financial inclusion rate based on solidarity financing of family units of MSEs in Trujillo (SCIÉNDO INGENIUM, 2026)
At present, microfinance client financing is based on an individual assessment of MSMEs with a low level of individual financial inclusion. Therefore, this research proposes to calculate an indicator of financial inclusion of adults in households with MSMEs in Trujillo. In the methodology, the indicator is calculated in function of the dimensions of use, access and quality of the financial products that attend the MSME segment and according to the human development index (HDI) used by the UNDP. The individual financial inclusion indicator of the households of Trujillo's MSMEs shows a result of 0.317, with 0 being no financial inclusion and 1 being total financial inclusion. And the indicator of financial inclusion based on solidarity financing of family units with MSMEs yields a result of 0.607, concluding that the indicator of financial inclusion of family units with MSMEs in Trujillo allows their financial inclusion much more than individual inclusion. In addition, with a Monte Carlo simulation, the variable with the highest level of sensitivity in the indicator is the amount of credit approved.
Keywords: Financial Inclusion; Solidarity Financing; MSEs; Family Unit; Microfinance